Study Of Various Types Of Pvd And Ph.D. Joints On Vertical Drainage Performance - Meylani Nurul Hidayah; Hary Christady Hardiyatmo; Agus Darmawan Adi (Publikasi Indonesia, 2023)
An important factor for increasing the effectiveness of the PVD (Prefabricated Vertical Drains) is the value of sufficient discharge capacity so that the PVD can work optimally. The use of PVD is usually accompanied by the use of PHD (Prefabricated Horizontal Drains) as horizontal drainage and combined with preloading. In the field, the connection is made by winding the PVD to the PHD and then tying it with cable ties. The connection system can cause deformation at the top of the PVD thereby reducing the effectiveness of the PVD discharge capacity. This study aims to find the optimal PVD-PHD connection system for the discharge capacity which is affected by confinement pressure, overburden pressure, and hydraulic gradient with a PVD-PHD connection system discharge capacity tester. The test specimens used were PVD (5mm thick; 100mm wide) and Ph.D. (20 mm thick; wide: 100 mm, 200mm, and 300mm). 4 types of connection systems have been tried, namely connections A1 and A2 where the PHD is connected in a horizontal position, and connections B1 and B2 where the PHD is connected in a vertical position. Of the four connection systems B1, the connection system has the largest discharge capacity value and a significant increase in PHD width from 100 mm to 300 mm with an increase of 7.694% at 50 kPa overburden pressure and 1.0 hydraulic gradient the highest compared to other connection types